SARS-CoV-2 vaccination in patients with multiple sclerosis in Germany and the United Kingdom: Gender-specific results from a longitudinal observational study - Jeff Rodgers (The Lancet Regional Health - Europe, 2022)
BackgroundVaccines offer people with multiple sclerosis (PwMS) an effective protection against severe COVID-19 disease courses. However, representative real-world data on the tolerability of SARS-CoV-2 vaccines in PwMS are limited. We aimed at analysing vaccination reactions (VRs) and MS deterioration following SARS-CoV-2 vaccinations in German and United Kingdom (UK) PwMS, especially regarding gender-specific differences.MethodsThe German Multiple Sclerosis Society and the UK MS Registry acquired health data via an online system following the first (X1) and second SARS-CoV-2 vaccination (X2), respectively: sociodemographic and clinical data, vaccines used, VRs, MS deterioration (worsened or new MS symptoms, Germany only) and relapses (Germany only). The frequencies of VRs and MS deterioration were analysed stratified by gender.FindingsFollowing X1 (X2), 2346 (1835) German PwMS and 3796 (683) UK PwMS participated in the study. The most frequent vaccination scheme was two-dose tozinameran for Germany (77·1%, 1424/1847) and two-dose AZD1222 for the UK (61·3%, 419/683). The most common VRs were fatigue, headache and pain (at the injection site) and occurred more often in women compared with men. German PwMS reported VRs more frequently after X2 vs. X1 (65·4% [1201/1835] vs. 61·2% [1435/2346]), while for UK patients it was the opposite (X1 vs. X2: 48·7% [1849/3796] vs. 30·0% [205/683]). MS deterioration occurred in 19·0% (445/2346) of the German PwMS without resulting in gender-specific differences. Fatigue and gait impairment were the most frequent deteriorated MS symptoms.InterpretationFemale PwMS reported experiencing VRs more often than men. Longitudinal data are needed to enable valid statements regarding long-term MS deterioration and long-lasting VRs.